2016
DOI: 10.1371/journal.pone.0154831
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cerebral Autoregulation during Head Up Tilt in Patients with Severe Brain Injury

Abstract: Early mobilization is of importance for improving long-term outcome for patients after severe acquired brain injury. A limiting factor for early mobilization by head-up tilt is orthostatic intolerance. The purpose of the present study was to examine cerebral autoregulation in patients with severe acquired brain injury and a low level of consciousness. Fourteen patients with severe acquired brain injury and orthostatic intolerance and fifteen healthy volunteers were enrolled. Blood pressure was evaluated by pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…The goal of the present study is to test whether LFO gains of cerebral hemodynamic variables, quantified by our innovative hybrid optical instrument, are useful biomarkers to distinguish two groups of cognitively healthy older subjects with high-or low-risk for developing CVD. Upon comparison with literature [21,26,[33][34][35][36][37][38][39], we believe this study is innovative in that: (a) it used an innovative hybrid optical instrument to simultaneously measure multiple cerebral hemodynamic parameters including rCBF, Δ[HbO 2 ] and Δ[Hb] in cerebral microvasculature. Multiple cerebral functional parameters provided more comprehensive assessment of brain activities than a single parameter alone, (b) it studied a unique population: cognitively healthy older subjects stratified by cerebrovascular risk and (c) it innovatively explored CAs (extracted from LFO gains of cerebral hemodynamics) as new biomarkers for diagnosis of CVD at preclinical stage.…”
Section: Study Innovationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of the present study is to test whether LFO gains of cerebral hemodynamic variables, quantified by our innovative hybrid optical instrument, are useful biomarkers to distinguish two groups of cognitively healthy older subjects with high-or low-risk for developing CVD. Upon comparison with literature [21,26,[33][34][35][36][37][38][39], we believe this study is innovative in that: (a) it used an innovative hybrid optical instrument to simultaneously measure multiple cerebral hemodynamic parameters including rCBF, Δ[HbO 2 ] and Δ[Hb] in cerebral microvasculature. Multiple cerebral functional parameters provided more comprehensive assessment of brain activities than a single parameter alone, (b) it studied a unique population: cognitively healthy older subjects stratified by cerebrovascular risk and (c) it innovatively explored CAs (extracted from LFO gains of cerebral hemodynamics) as new biomarkers for diagnosis of CVD at preclinical stage.…”
Section: Study Innovationsmentioning
confidence: 99%
“…TCD/NIRS has been used to measure LFOs in CBFV/ cerebral blood oxygenation for CA assessment [33][34][35][36]. Different orthostatic protocols were applied to induce MAP fluctuations for evaluating dynamic CA including a sit-stand maneuver [37] and tilting bed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data management plan and standard operating procedure are kept at the Copenhagen Trial Unit. * The standard deviation of the CRS-R was estimated from the change value of two studies and used to estimate the minimal relevant difference (SD/2) [23,24] ** The standard deviation of the EFA score was estimated from two observational studies investigating patients with brain injury approximately 1.5 months after injury and used to estimate the minimal relevant difference (SD/2) [25,26] *** The FIM standard deviation and minimal relevant difference has been investigated in two studies on patients with brain injury [16,17] Supplementary table 2. Exploratory clinical outcome for baseline, end of intervention, three-months and one-year.…”
Section: Fundingmentioning
confidence: 99%
“…Neither the physiological mechanisms causing orthostatic hypotension nor those that enable recovery from this phenomenon have been thoroughly investigated. Considering analysis of electrocardiography (ECG) signals obtained from ABI patients during HUT, we suggested that impairment of baroreceptor sensitivity may be involved [ 8 ]. Whether the impairment is caused by the brain lesion per se or prolonged immobilisation or both remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%